Reciprocal Relationships and Well-being Implications for Social Work and Social Policy - Törrönen, Marritta (Taylor & Francis, 2017)
This book provides a robust empirical and theoretical analysis of reciprocity and its implications for social work and social policy practices by discussing how ideas of reciprocity can be understood and applied to welfare policy and social care practices, as well as how the act of reciprocity supports the wellbeing of citizens.